Prospective for the semantic web: technological divergence and linked data markets creation - Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2012)
This paper shows some trends that are currently occurring in the environment of the semantic web. More specifically it presents schema.org, a project developed by Google, Yahoo and Bing for semantic markup using microdata, Freebase, a knowledge bank for structured information and Kasabi, a platform that operates into the modality of "Software as a Service" for the publication and commercial distribution of semantic data. It is possible see some technological divergence in the application of semantic Web standards with the development of new proposals as microdata, and the emergence of a market for linked data through publishing platforms that facilitate commercialization.
Keywords: Semantic web; Linked open data; Microdata; RDF; a Schema.org; Kasabi; Freebase; SaaS; Semantic data market; Technological divergence.